ANALISIS YURIDIS PENGELOLAAN OBAT HEPATITIS B BERSUBSIDI DALAM SISTEM FARMASI RUMAH SAKIT DI INDONESIA - Maria Aryanthi Ledjap; Ramlin Ahmad; Muhammad Syafi’i (Universitas Kapuas, 2026)
The management of subsidized Hepatitis B medicines in hospital pharmacy systems remains vulnerable to administrative irregularities, ethical violations, and legal non-compliance, potentially undermining patients’ rights to equitable and transparent healthcare. This study analyzes the juridical framework governing such management and examines deviations in practice along with resulting legal responsibilities. Using a normative juridical method with statutory, conceptual, and case approaches, this research relies on primary, secondary, and tertiary legal materials analyzed qualitatively. The findings indicate that despite comprehensive pharmaceutical regulations in Indonesia, implementation at the hospital level has not fully reflected principles of transparency, accountability, and justice. Deviations include maladministration, misappropriation in drug distribution, and weak internal supervision. These conditions result in layered legal consequences, including administrative sanctions, ethical liability, and potential criminal responsibility. Strengthening regulatory enforcement, improving pharmaceutical audits, and enhancing legal awareness are necessary to ensure accountable and equitable management of subsidized medicines.